Infrared investigation of barite and gypsum crystallization: Evidence for an amorphous to crystalline transition - Jones, Franca (The Royal Society of Chemistry, 2012)
Infrared was used to monitor the progression of barite (BaSO4) and gypsum (CaSO4·2H2O) crystallization. It was found that barite crystallized with broad infrared peaks that narrowed over time. This was accentuated when an inhibitor was added. The infrared of gypsum in the early stages showed a phase that was clearly different to either bassinite or gypsum. It is hypothesised that in the absence of inhibitors, the rate-determining step for barite crystallization is the transformation from a disordered solid to a crystalline solid as little water was observed to be present during this process when inhibitors are not present. All of these findings are consistent with a non-classical model of crystallization where disordered solids eventually rearrange to a crystalline solid if not inhibited. It also suggests that water may be key to determining the “lifetime” of the disordered clusters.